Pengaruh Citra Merk, Kualitas Produk, Harga, dan Promosi terhadap Kepuasan Konsumen Pengguna Motor Honda Beat - Agus Hariyanto; Ari Susanti (Target : Jurnal Manajemen Bisnis, 2021)
The study was conducted to determine the effect of brand image, product quality, price and promotion on consumer satisfaction. The variables used in this study include brand image (X1), product quality (X2), price (X3), promotion (X4) and consumer satisfaction (Y). This research was conducted with a quantitative approach with a sampling method using purposive sampling using roscoe count so that 100 respondents who use Honda Beat can be taken. Data collection techniques with a Likert scale to make it easier for respondents to fill out the questionnaire. The data analysis used is multiple linear regression analysis using SPSS tools to see the results of the data obtained. The results showed that brand image, product quality, price and promotion had a positive and significant influence on consumer satisfaction.